Increased Serum Alkaline Phosphatase in a FeLV-Positive Cat - Valle, Stella de Faria; Elesbão, Bárbara Schwarzbach; da Costa, Fernanda Vieira Amorim; Gambin, Laís Stefen; de Jesus, Luciana; Moresco, Mauricio Bianchini; Bettio, Marcelle; González, Félix Hilário Dias (Acta Scientiae Veterinariae, 2016)
Background: Feline Leukemia Virus (FeLV) is an oncogenic virus that usually invades bone marrow causing non-regenerative anemia and thrombocytopenia. In FeLV positive cats, the myeloid leukemia is characterized by intense proliferation of blast cells in a bone marrow with myeloid precursor predominance and several malignancies degree. The leukocyte alkaline phosphatase is found secondary granules of mature neutrophils of humans, horses and cows but not in dogs and cats, which demonstrate the enzyme activity in myeloblast and promyeloblasts cells. In this case is describing a FeLV-positive case with leukemic disorder accompanied by extremely high levels of serum alkaline phosphatase. Case: A 8-year-old castrated male Domestic Short Hair cat with a 3-month history of convulsions, pica, vomits, lethargy, hypodipsia and anorexia was examined and showed mild dehydration, severe jaundice and hyperpnoea. Laboratory results evidenced severe normocytic hypochromic non-regenerative anemia, moderated leukocytosis with severe degenerative neutrophil left shift, moderated lymphocytosis and severe thrombocytopenia. Serum biochemical profle showed mild hy peralbuminemia, moderated increment in alanine transaminase and severe increment in alkaline phosphatese. The cat was positive for ELISA point of care FeLV antigen and negative for FIV antibodies. Urinalysis revealed moderated bilirubinuria and proteinuria. The bone marrow cytology showed high cellularity, increased of M:E ratio, rare megakaryocyte lineage, erythroid hypoplasia, myeloid hyperplasia with blast excess and dysgranulopoiesis. Discussion: FeLV is a virus that usually causes cytopenias and in this case this was well evidenced through a severe non regenerative anemia and thrombocytopenia. Generally, anemia is a non-neoplastic complication of FeLV mainly related to suppressive effects hematopoietic and stromal cells of the bone marrow. Nevertheless, in this case, the anemia also may be attributable to the observed acute myeloid leukemia. Neutrophilia is an uncommon fnding in FeLV-infected cats, even more with the severe degenerative left shift as in the present case. This fnding could be associated to a myeloid hyperplasia. Some biochemical alterations, as hyperalbuminemia and increment in values of serum ALT could be explained by clinical observations like dehydration and some degree of hepatic enlargement, respectively. However, the excessive value for serum alkaline phosphatase activity is an unpublished fnding in cats. In humans high levels of ALP has been associated with neutrophilia and it is quite likely that a great amount of degenerative neutrophils may contribute for high leakage of ALP than in other circumstances of neutrophilia. This is the frst report of a FeLV-positive cat exhibiting extremely high serum values of the enzyme ALP, possibly attributable to acute myeloid leukemia. Keywords: neutrophilia, cytopenia, non-regenerative anemia, acute leukemia.